Determining the critical factors of eWOM about corporate social responsibility on social networking sites: End users’ perspective - Hu, Yuchen; Tang, Qingbo; Wang, Xuan; Ali, Shahid (Frontiers in Psychology, 2022)
It is now possible to propagate CSR information through social media platforms. Electronic word of mouth (eWOM) directly impacts image and upcoming portfolios of the organization. Customers, employees, and other stakeholders generate revenue for the company. Our goal was to understand why people were sharing and commenting in response to terrible reports about corporate social responsibility (CSR) on WeChat. A company's desire to comment on and share CSR news and its perception of its own social and environmental responsibility were all presumed explanatory variables in our investigation. 315 WeChat users were asked to grade a fictitious news report of the environment. The results were shocking. According to our findings, an individual's attitude toward actions and the effectiveness of information directly correlates to their social and environmental awareness level. EWOM may be discouraged by a company's brand name, which has the potential to harm its reputation with its customers.